Analisis Pengembangan Kurikulum Pendidikan di Madrasah Aliyah Negeri Insan Cendikia Serpong Jakarta - Ardiansyah, Ardiansyah; Latif, Mukhtar; Us, Kaspul Anwar (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2024)
The development of educational curricula at Islamic educational institutions greatly determines the quality of these institutions. This research aims to analyze and describe the development of the educational curriculum at Madrasah Aliyah Negeri Insan Cendikia Serpong Jakarta. This research method uses a descriptive qualitative approach, while data collection techniques in this research use observation, interviews and documentation, with data analysis techniques using data reduction, data presentation and drawing conclusions. The results of this research show that MAN Insan Scholar Serpong (MAN IC Serpong) is a model of secondary education unit that integrates Islamic Religious Education with science and technology in a balanced manner. This approach aims to be a pioneer in overcoming the divide between religious knowledge and science and technology. The advantages of MAN IC Serpong can be seen in curriculum development, Information and Communication Technology (ICT) based management, learning facilities, professionally managed dormitories, and daily communication using Indonesian and international languages.